A new technique for 3D printing dielectric structures using aerosol-jettable photopolymers. (1st March 2023) - Areias, Christopher; Piro, Yuri; Ranasingha, Oshadha; Akyurtlu, Alkim
Abstract: In this article, we report the development of a new method for the 3D printing of dielectrics. An aerosol-jet printer is used to deposit overlapping layers of photopolymer material under ultraviolet floodlight in the assembly of ramping microstructures in situ without the need for supporting structures. Printing is conducted using an in-house photodielectric ink, the development of which is presented with an emphasis on dielectric and mechanical bulk material characterization. Low dielectric loss at the X-band and structural strength are demonstrated, followed by print characterization wherein the driving mechanisms of the new method are explored, tied to print conditions, and related to specific material properties. Finally, a complex structure in the form of a 3D flower is printed to demonstrate the controlled and repeatable performance of the proposed technique.